Pharmacological Evaluation Of Herbal Extracts For Their Invitro Hypoglycemic Activity - A.PADMANABHA RAO; KAISER JAMIL (International Journal of Pharma and Bio Sciences, 2011)
Diabetes mellitus is a metabolic disorder and the management is an important criterion for pharmacotherapy. The medicinal plants play very important role in preventing the progress of the disease. Present study deals with screening of polyherbal extracts using in-vitro techniques for its antidiabetic activity. The plants used in the study are Eugenia jambolana and Cinnamomum zeylenicum. The polyherbal extracts were subjected to in-vitro evaluation using cell culture assays, α-glucosidase inhibition and antioxidant property. The cell lines 3T3L1 C2C12 and HepG2 were used to measure the uptake of glucose. The results showed that the glucose uptake was more in APKJ-004 polyherbal extract when compared with other extracts. α-glucosidase inhibitory activity was found in all the extracts and they were comparable to the standard acarbose and the highest inhibitory activity was found in the polyherbal extract APKJ004 (IC50147.2µg/ml). In-vitro antioxidant potential revealed that the extract APKJ004 is more potent and is comparable to the standard. Based on in-vitro evaluations, unique combination of glucose uptake activity and α glucosidase inhibition potential of extract APKJ-004 with prominent hypoglycemic activity will aid in the treatment of diabetes mellitus.